Using urban triage to plan for walkability - Holt, Steven (Kansas State University, 2015)
Literature shows that walkable neighborhoods have the potential to significantly decrease the carbon footprint of cities by lessening the need to drive, as well as providing many health, economic, and social benefits to society. The goal of this research, therefore, was to devise a practical strategy to create walkable places in the car-oriented city of Wichita, Kansas. A necessary component of this strategy is an “urban triage,” described by Jeff Speck in Walkable City as identifying streets with the most existing potential and concentrating limited resources to their improvement (2012, 254). This report employed an urban triage of Wichita at two scales based on three central characteristics of walkability: urban fabric, dense street network and connectivity. Comparing block length and link to node ratio, I built a case for downtown, which is organized on a traditional grid of streets, over a typical shopping district organized around the more modern hierarchical pattern of streets. Within downtown, I further narrowed the study area primarily based on urban fabric, the degree to which streets are enclosed by buildings. I created a method to measure urban fabric, using aerial imagery and street views, taking into account the consistency of the street wall, height of buildings and foreground. The strongest complete corridor, in terms of urban fabric, and three potential links between that corridor and downtown’s largest event space, became the study area for further analysis. A rubric, based on characteristics of walkability extrapolated from literature, served as the instrument to measure the attributes of each block in the study area. Each attribute, as well as the characteristics that they create, yielded a map, contrasting strong and weak blocks. This analysis provided the detailed information necessary to create an informed conceptual strategy to resolve these weaknesses. Selective building infill resolved gaps in the urban fabric, road diets and improved crossings restored modal balance to the street, and a new pedestrian corridor completed a broken street and activated an existing park.
Keywords: Urban triage; Walkability; Landscape Architecture (0390); Urban Planning (0999)